Mitochondrial dysfunction generates a growth-restraining signal linked to pyruvate in Drosophila larvae. Issue 1 (2nd October 2019) - George, Jack; Tuomela, Tea; Kemppainen, Esko; Nurminen, Antti; Braun, Samuel; Yalgin, Cagri; Jacobs, Howard T.
ABSTRACT: The Drosophila bang-sensitive mutant tko 25t, manifesting a global deficiency in oxidative phosphorylation due to a mitochondrial protein synthesis defect, exhibits a pronounced delay in larval development. We previously identified a number of metabolic abnormalities in tko 25t larvae, including elevated pyruvate and lactate, and found the larval gut to be a crucial tissue for the regulation of larval growth in the mutant. Here we established that expression of wild-type tko in any of several other tissues of tko 25t also partially alleviates developmental delay. The effects appeared to be additive, whilst knockdown of tko in a variety of specific tissues phenocopied tko 25t, producing developmental delay and bang-sensitivity. These findings imply the existence of a systemic signal regulating growth in response to mitochondrial dysfunction. Drugs and RNAi-targeted on pyruvate metabolism interacted with tko 25t in ways that implicated pyruvate or one of its metabolic derivatives in playing a central role in generating such a signal. RNA-seq revealed that dietary pyruvate-induced changes in transcript representation were mostly non-coherent with those produced by tko 25t or high-sugar, consistent with the idea that growth regulation operates primarily at the translational and/or metabolic level.